Photovoltaic energy yield predictions using satellite data - Peters, Ian Marius; Liu Haohui; Buonassisi, Tonio (Proceedings of SPIE - The International Society for Optical Engineering, 2020)
Energy yield is a key metric for evaluating the performance of photovoltaic systems. It describes the total amount of energy generated by a photovoltaic (PV) installation over a given period, typically a year, and depends on physical properties of the solar cell like efficiency, band gap and temperature coefficient, as well as the operating conditions in a given location. Because the response of a solar cell to these conditions varies, two photovoltaic technologies may have a different energy yield, even if their lab efficiency is identical. Predicting energy yield accurately is important to system operators and installers to estimate the technical and economic performance of a PV installation. In this paper, we summarize our findings about satellite based energy yield predictions of solar cells with various technologies.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Energy Yield; Modelling; Photovoltaics